Pancreatoduodenectomy With Arterial Resection for Locally Advanced Pancreatic Cancer of the Head: A Systematic Review. Issue 5 (May 2020) - Haines, Morgan; Chua, Terence C.; Jamieson, Nigel B.; Mittal, Anubhav; Gill, Anthony J.; Samra, Jaswinder S.
Abstract : Abstract: The development of increasingly effective chemotherapy regimens and increasing tumor necrosis is allowing radical pancreatectomy to be re-evaluated. This systematic review examines the outcome of patients with locally advanced cancer of the pancreatic head after pancreatectomy with arterial resection. Electronic searches were performed on PubMed and Medline databases between January 2000 and December 2018. The end points were to determine the safety and overall survival after arterial resection in pancreatectomy. Thirteen studies with 467 patients were included. Celiac, hepatic, mesenteric, and splenic arteries were resected across all studies. The median overall morbidity was 52% (range, 37%–100%) and with major complications occurring in a median of 25% (range, 12%–54%) of patients. The median 90-day mortality was 5% (range, 0%–17%). R0 was achieved in 66% (range, 43%–100%) and R1 in 31% (range, 0%–74%). The median survival was 17 (range, 7–29) months with a 1- and 3-year survival of 59% (range, 16%–92%) and 17% (range, 0%–13%), respectively. Pancreatectomy with arterial resection may be safely performed in high-volume centers with acceptable survival results in highly selected patients. Pooling of data through a multi-institutional registry will allow a more accurate assessment of the safety and efficacy of this treatment strategy.